Soft Palate Morphology and Nasopharyngeal Airway In the Subgroups of Skeletal Class III Malocclusion - Ayşe Tuba Altuğ-Ataç; Gökmen Kurt (Galenos Yayinevi, 2006)
This study was performed to evaluate and compare the soft palate morphology and nasopharyngeal airway relations of persons with skeletal Class III malocclusions originated from; maxillary retrusion, mandibular protrusion and the combination of maxillary retrusion and mandibular protrusion. Lateral cephalometric radiographs of 66 subjects were divided into three groups according to the Nperp-A and Nperp-Pg variables; Group 1-maxillary retrusion (n: 23; mean age: 13.44 years), Group 2-mandibular protrusion (n: 22; mean age: 13.31 years), and Group 3-combination of maxillary retrusion and mandibular protrusion (n: 21; mean age: 13.04 years). The differences between all Class III groups were evaluated by Analysis of Variance (ANOVA) and Duncan test. Significant differences of the craniofacial structures were observed between all three groups in Nperp-A and SNB (p<0.001); Group 1 and Groups 2 and 3 in Nperp-Pg (p<0.001); Group 2 and Groups 1 and 3 in SNA (p<0.001); Groups 2 and 3 in ANB (p<0.001). Significant differences in nasopharyngeal relations were observed between Groups 2 and 3 in SPL/IPS (p<0.001), SPT-PPW2 (p<0.01) and SPL/SPS (p<0.05). However, the morphology and angulation of the soft palate were similar between all groups. The pharyngeal airway dimensions are greater; the soft palate length is shorter in patients with prognathic mandibles (Group 2), followed by maxillary retrusion and maxillary retrusion combined with mandibular protrusion patients.